Manajemen Keselamatan Lalu Lintas di Jalan Tol Trans Jawa Ruas Semarang-Batang - Putri, Ditha Andriyani; Widowati, Evi (Indonesian Journal of Public Health and Nutrition, 2021)
Background: The number of traffic accidents that occurred on the Semarang-Batang Trans Java Toll Road from 2018 to 2019, were 201 incidents with 326 victims and 12% died, 25% were seriously injured and 63% slightly injured. Accidents are caused by drivers, vehicles, roads and the environment. Traffic safety management is developed as an effort to prevent and control the risk of traffic accidents. The purpose of this study was to determine the description of traffic safety management on the Trans Java Toll Road Semarang-Batang, Central Java. Methods: This type of the research is quantitative descriptive involved Traffic Management & Maintenance Manager, Patrol Supervisors, and Patrol Officers. This research instrument used observation sheets, interview guides, and documentary study sheets. Data were analyzed by univariate analysis. Results: The results of this study show that from 80 indicators of Toll Road Traffic Safety Management, the indicators already applied are 69% (55 indicators) and which have not been implemented are 31% (25 indicators). Conclusion: The implementation of traffic safety management efforts on the Trans Java Toll Road Semarang-Batang Section was not fully compatible according to all points of regulation used in this study.